Beyond Business Creation: How Entrepreneurship Education Shapes Entrepreneurial Mindsets among University Students in Indonesia - Yeldy Dwi Genadi; Adrianda Anwar; Zamroni Alpian Muhtarom (Future Techno-Science, 2026)
Entrepreneurship education is increasingly expected to prepare university graduates for uncertain labor markets, yet much of the literature still evaluates its effectiveness through entrepreneurial intention rather than through deeper changes in how students think, interpret problems, and create value. This study aimed to explain how entrepreneurship education shapes entrepreneurial mindsets among university students in Indonesia. A qualitative interpretive design was used, drawing on semi-structured interviews with undergraduate students who had completed entrepreneurship courses involving project-based assignments, business simulations, mentoring, pitching, and reflection. The data were analyzed using thematic analysis and interpreted through Experiential Learning Theory. Five interrelated themes emerged: opportunity recognition through experiential tasks, confidence development through practice-based learning, failure as a trigger for resilience, social interaction as a catalyst for entrepreneurial thinking, and reflective learning as the mechanism of mindset transformation. The findings show that entrepreneurship education does not merely transmit business knowledge or increase startup intention; it gradually reframes how students perceive problems, uncertainty, feedback, and failure. The study contributes by positioning entrepreneurial mindset as an experiential, socially mediated, and reflective learning outcome, particularly in the context of higher education in an emerging economy. These findings suggest that universities should design entrepreneurship education as an integrated learning journey that combines authentic tasks, safe failure, mentoring, teamwork, and structured reflection.